Data envelopment analysis (DEA) as a contribution to the teaching of agricultural sciences (Revista de Ciências Agroveterinárias, 2015)
This paper addresses the importance of the discipline of Agricultural Efficiency and Planning for courses in agricultural sciences, with some basic concepts about DEA analysis (data envelopment analysis). It aims to evaluate the relative efficiency of the notes, coefficient of performance and absences of students taking this course, through the DEA analysis, by UNESP – Ilha Solteira, Brazil. Methodologically, the BCC model and the output orientation, in order to consider the maximization of notes and correlation coefficient (outputs), given the absences recorded (input) for each of the 27 students. It is noted that a 27.14% reduction in the overall average among students, compared to the best effieiency of the class, showed the coefficient of performance at 9.84%, and that the differences between targets and actual log data demonstrate the relationship variables that can make efficient representation of the ideal outputs. We conclude that the DEA analysis proved to be an important tool to evaluate discipline, serving as a reference for teachers to establish goals that encourage having a better standard of academic performance, extended also to other disciplines.
Keywords: teaching; assessment; DEA analysis.